2018
DOI: 10.1111/gbi.12290
|View full text |Cite
|
Sign up to set email alerts
|

A tale of two eras: Phytoplankton composition influenced by oceanic paleochemistry

Abstract: We report the results of simple experiments which support the hypothesis that changes in ocean chemistry beginning in the Mesozoic Era resulted in an increase in the nutritional quality per mole of C and per cell of planktonic algal biomass compared to earlier phytoplankton. We cultured a cyanobacterium, a diatom, a dinoflagellate, and a green alga in media mimicking aspects of the chemistry of Palaeozoic and Mesozoic-Cenozoic oceans. Substantial differences emerged in the quality of algal biomass between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…Diatoms are important oceans' primary producers, which strongly affect global food webs. From a biological perspective, the world of diatoms has been moulded by the competitive interactions with other phytoplankton groups, resulting in the spatial patterns of marine primary production observed today (Armbrust, 2009;Vallina et al, 2014;Vincent and Bowler, 2020), and by the coevolution with copepods and other micro-predators that have influenced radiation trajectories from higher levels of food webs (Turner, 2004;Hamm and Smetacek, 2007;Giordano et al, 2018;Lürling, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Diatoms are important oceans' primary producers, which strongly affect global food webs. From a biological perspective, the world of diatoms has been moulded by the competitive interactions with other phytoplankton groups, resulting in the spatial patterns of marine primary production observed today (Armbrust, 2009;Vallina et al, 2014;Vincent and Bowler, 2020), and by the coevolution with copepods and other micro-predators that have influenced radiation trajectories from higher levels of food webs (Turner, 2004;Hamm and Smetacek, 2007;Giordano et al, 2018;Lürling, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These findings allowed to mechanistically connect the information available on ocean paleochemistry to the observations on changes in phytoplankton composition and morphology in the early Mesozoic [17,72]. The experiments in Giordano et al [51] also highlight the importance of inter-and intraspecific interactions in the utilization of resources and cell composition [124,125]: the changes in the composition of algae was in fact different whether algae were exposed to the reconstructed paleochemistry in monospecific or multispecific cultures.…”
Section: Evolution Of Functionsmentioning
confidence: 83%
“…The combination of state of the art FTIR spectroscopy [33,43,65,86,87] and consideration on ecological stoichiometry [47] showed that chemical changes at the end of the Paleozoic profoundly altered algal cell composition, making it better suited as food for micrograzers. It was concluded that the increased activity of micrograzers may have been fueled by these compositional changes and, in turn, more active micrograzers exerted a selective pressure on algae that favored the red lineage clades, better equipped to respond to their aggression [51]. These findings allowed to mechanistically connect the information available on ocean paleochemistry to the observations on changes in phytoplankton composition and morphology in the early Mesozoic [17,72].…”
Section: Evolution Of Functionsmentioning
confidence: 98%
See 1 more Smart Citation
“…This may also have relevance from a historical/evolutionary point of view: the stoichiometric alterations that occurred in phytoplankton during the transition from the Paleozoic to the Mesozoic‐Cenozoic oceans, due to changes in the chemical environment of the oceans, may have driven profound modifications in the relationships between algae and their predators and fueled the appearance of more efficient grazers (Giordano et al. ). Our results would also provide a new viewpoint over the evolutionary trajectories of algae and their predators: if cell composition influences the survival of algae to grazing, it may be targeted by natural selection and may not only have played a major role in structuring the trophic webs of the oceans but also contribute to shape the oceans of the world that awaits us.…”
Section: Discussionmentioning
confidence: 99%